Effect of metal concentration on growth and luminescence of luminous bacteria straims isolated from golfo de Nicoya, Costa Rica - Vega-Corrales, Luis (2021)
Luminescence in bacteria is catalyzed by luciferase. When these microorganisms are exposed to toxic substances, the bioluminescent enzyme system can be inhibited. The objective of this study was to analyze the potential that these microorganisms offer as native bioindicators of coastal marine pollution. The dynamics of luminescence intensity by visual classification and the effect of metal concentration on the growth and luminescence of 25 strains of luminescent bacteria, isolated during 2016 from seawater samples from the gulf of Nicoya, Costa Rica, was evaluated by the disk diffusion method. The sensitivity of each strain to different concentrations (0.1, 0.5 and 1 mg mL-1) of Cd, Cu, Cr, Pb and Zn was determined by its bioluminescent phenotype. In susceptible strains, a range of metal concentrations less than the growth inhibitory concentration affected the expression of luminescence. Strains with intense luminescence and defined zones of luminescence inhibition were considered to have greater potential as native bioindicators for monitoring environmental toxicity. More studies are required to determine the minimum concentrations that inhibit growth and luminescence with respect to the tested metals and other potentially toxic substances for the coastal marine ecosystems of Costa Rica.